Passive time reversal probe-signal capture optimization for underwater communications - Silva, A. (2014)
Passive Time Reversal (pTR) is an emerging technique for underwater communications where a channel probe is sent ahead of the data packet. The channel probe must be captured in a time window for post crosscorrelation with the data. The Signal to Noise Ratio (SNR) of pTR, and hence the detector error rate, will be dependent on the starting point and duration of this time window. Typically the beginning and length of the time window should depend on the time dispersion of the acoustic channel which, in turn, depends on the environment properties and on the experimental geometry. Heuristic reasoning would suggest that if a short time window fails to include all significant multipath it will result in imperfect focusing, while an overly long window will reduce the efficiency of the communication system by introducing additional noise in the pTR system. That problem calls for an optimization that has previously been addressed only heuristically. In order to bring the pTR capabilities to a practical modem the engineering problem of time window automatic optimisation must be solved, and that is the main purpose of our paper. An expression for the optimal pTR SNR time window length is presented and its validity confirmed with simulations and real data from the INTIFANTE’00 sea trial.